A reasearch proposal into the practice of outsourcing of facilities management - Baba, Maizan; Mohammed, Abdul Hakim (2005)
This working paper aims to justify the need to research into the operations, supervision and monitoring mechanisms of facilities management outsourcing. From the findings, the research proposes to develop a contractual framework for managing the facilities outsourcing contract. The objective is to help ensure that the services provided meet the requirement of the users and customers. The framework will be developed based on the best practice in international environment. Outsourcing is an organizational agenda. Its performance will strategically affect the business of the organization. Outsourcing involves a number of parties namely the client, service provider, users and customers of the client organization. This nature of transaction requires for suitable operational, supervisory and monitoring mechanisms to succeed. It has to fulfill the benefits expected by the client. This nature of transaction also has certain risks and has the potential to fail the outsourcing venture. The management of outsourcing of facilities management comes with pressures from the above transacting parties including the technologies and business of the client organization. Researches in the practice of outsourcing have also focused on the factors to ensure successful facilities management outsourcing. However, there is still the need to investigate further the issue to help the client and service provider to achieve the benefits of outsourcing especially in the health industry. None of the researches were conducted from the combined perspectives of the client, service provider, users and users. In fact there were also no researches conducted with the client, service provider and users as respondents. Only one research took the view of both the client and service provider. The rest of the researches focused on the view of the client or users separately. In Malaysia, the researches conducted were in logistics and facilities management (i.e. building cleaning). Therefore, there is so much opportunity for researches into outsourcing practice including in facilities management. At the same time there are many big outsourcing projects implemented in the public as well as private sectors. The government hospitals support services privatization project is an outsourcing project that is into its second-half of the 15 years concession period; the concession may be negotiable for further extension. There is the need to re-assess and re-evaluate the performance of the whole outsourcing contract to ensure it really meets the requirements and benefits expected by the users. The operations, supervision and monitoring mechanisms need to be re-looked to identify the weaknesses and to come-up with the solutions so that the users (doctors, medical assistants, nurses, attendants and other health workers) are satisfied with services that meet their requirement which is necessary for them to provide quality health care to the patients.